Peningkatan Hasil Belajar IPS melalui Pembelajaran Kooperatif Model Numbered Head Together (NHT) Masa Covid 19 pada Siswa Kelas VIII-4 SMPN 2 Keruak - Sardana, Teguh (Lembaga Yasin AlSys, 2021)
This type of research is classroom action research (CAR). The target of this research is the students of class VIII-4 SMPN 2 Keruak. The purpose of this classroom action research (CAR) is to determine the extent to which students' learning outcomes in social studies are improved by applying the Nimbered Head Together Method. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken it is proven to be able to improve student learning outcomes by achieving the classical mastery that is set at 85%. Classical completeness of 81.25% was obtained in the first cycle, it could increase in the second cycle to 93.75%. In terms of student activity, there was also an increase, namely in the first cycle, the moderately active category increased to an active category. The results of this action research indicate that the application of the Numbered Head Together Method can improve student learning outcomes in social studies lessons with completeness reaching 100%.